2013
DOI: 10.1371/journal.pone.0068774
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Induced Expression of Alx3 That Is a Positive Regulator of Osteoblast Differentiation

Abstract: Bone morphogenetic proteins (BMPs) regulate many aspects of skeletal development, including osteoblast and chondrocyte differentiation, cartilage and bone formation, and cranial and limb development. Among them, BMP-2, one of the most potent osteogenic signaling molecules, stimulates osteoblast differentiation, while it inhibits myogenic differentiation in C2C12 cells. To evaluate genes involved in BMP-2-induced osteoblast differentiation, we performed cDNA microarray analyses to compare BMP-2-treated and -unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As one of the most important regulatory factors for bone formation, BMP-2 has been proved to have strong ability in promoting bone cell differentiation and inducing bone formation in vitro 25,26. Runx2 expression and activation is considered another crucial point incorporating many signals that regulate osteoblast differentiation 27.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important regulatory factors for bone formation, BMP-2 has been proved to have strong ability in promoting bone cell differentiation and inducing bone formation in vitro 25,26. Runx2 expression and activation is considered another crucial point incorporating many signals that regulate osteoblast differentiation 27.…”
Section: Discussionmentioning
confidence: 99%
“…BMP plays an essential role in bone growth and wound repair. Active mesenchymal cells are the target cells of BMP (21). Under the induction of BMP, muscular and perivascular mesenchymal cells can be differentiated into osteocytes, a process that is specific and irreversible (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that BMP-2 may first combine with and activate Type II and I receptors on the surface of the membrane (23). Secondly, intracellular signal transduction pathways of Smad may then be activated to induce the transcription of intranuclear target genes and protein expressions (21). Novel research has suggested that BMP-2 is the most representative in BMP family, with relatively high contents (23).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important regulatory factors for bone formation, BMP-2 has been proved to have strong ability in promoting bone cell differentiation and inducing bone formation in vitro [27,28] . High expression of BMP-2 in bone marrow stromal cells can promote bone marrow stem cells to differentiate into osteoblasts, thus promoting the formation of bone [29] .…”
Section: Discussionmentioning
confidence: 99%